Integrated attitude determination and control system via magnetic measurements and actuation only - Mohammad Abdel Rahman, Mohammad Ibraheem; Sang-Young, Park (2009)
A nonlinear control scheme using a Modified State–Dependent Riccati Equation MSDRE has been developed through a pseudo-linearization of spacecraft augmented dynamics and kinematics. The full-state knowledge, required for the control loop is provided through a generalized algorithm for spacecraft three-axis attitude and rate estimation based on the utilization of magnetometer measurements and their time derivatives, while the control torque is generated via magnetorquers. The resulted attitude determination and control system has shown the capability of estimating the attitude better than 5 deg and rate of order 0.03 deg/sec in addition to maintain the pointing accuracy within 5 deg in each axis with pointing stability of less than 0.05 deg/sec.